Nosherwan ki baiti - Maqbool jhangir, maqsood (Ferozsons (Pvt) Limited ; Lahore, 2012)
"Nosherwan Ki Baiti" by Maqbool Jhangir is a historical novel that weaves a tale of courage, wisdom, and sacrifice, set against the backdrop of the Persian Empire, highlighting the life and struggles of a powerful and influential woman.